Factors Affecting Community Readiness for Tourism Village Development through Sidomukti Park Tourism Objects - ABDUL AZIS; Adrianto, Dimas Wisnu; Hasyim, Abdul Wahid (Graduate School, Universitas Brawijaya, 2024)
Community readiness has been conceptualized in the literature as a multidimensional construct that combines community attitudes, perceptions, and knowledge of issues; perceived level of preparedness; resources, including existing efforts around a particular problem; and leadership—measuring Community Readiness Model (CRM), which produces how ready a community is to take collective action. The research aims to provide factors influencing community readiness, especially in developing a sustainable tourist village through the Sidomukti Park tourist attraction. Sidomukti Village was chosen because of a new sustainable tourism village development project in the form of the Sidomukti Park tourist attraction. Regional Spatial Plan of Bojonegoro Regency Year 2021-2041 also states that Sidomukti Village embodies a tourism cultivation area. The method and approach used in this research is quantitative with CRM assessment, which is then analyzed using SEM (Structural Equation Modeling) analysis to obtain factors that influence community readiness in developing tourist villages. Based on the calculation, it can be seen that the level of community readiness in Sidomukti Tourism Village is included in the initiation stage, with a readiness level score of 3.65. In addition, based on the SEM-PLS results, it can be seen that the factors influencing community readiness in Sidomukti Tourism Village are community knowledge about issues/problems, community knowledge about efforts, community climate, and resources.